In-silico of Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) Inhibitors of Seven Bioactive Compounds from Sonneratia alba - Latief, Madyawati; Melani, Fitria; Yusnaidar, Yusnaidar; Tarigan, Indra Lasmana (Chimica et Natura Acta, 2025)
Cancer is a disorder resulting from genetic changes, abnormal growth, and spread to other parts of the body. Cancer treatment is commonly administered through chemotherapy, which often results in adverse side effects. Therefore, research is essential to identify safer alternative cancer therapies. This study aims to identify potential bioactive compound ligand receptor targets from Sonneratia alba as anticancer candidates in silico by identifying VEGFR target proteins based on their pharmacophores and studying their interactions through the reverse docking method. Docking simulations between the native ligand (Tivozanib) and the receptor yielded promising results, with a free energy value of -12.76 kcal/mol and an inhibition constant of 440.70 μM. Among the seven bioactive compounds, Meperidine (C15H21NO2) exhibited favorable outcomes, showing a free energy value of -7.39 kcal/mol and an inhibition constant of 3.83 μM. Additionally, the meperidine and gibberellin A7 compounds formed three and four hydrogen bonds, respectively, including one with Ala866, and interacted with 15 and 18 amino acid residues, such as Glu917, Cys919, Glu885, and Asp1046. The presence of active sites on the ligand or test compounds that bind to the target receptor indicates a potential for comparable affinity in inhibiting VEGFR-2 receptor activity.